2005
DOI: 10.1016/j.molcel.2005.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of RNA Polymerase II and Transcription Bubbles by XPG, CSB, and TFIIH: Insights for Transcription-Coupled Repair and Cockayne Syndrome

Abstract: Loss of a nonenzymatic function of XPG results in defective transcription-coupled repair (TCR), Cockayne syndrome (CS), and early death, but the molecular basis for these phenotypes is unknown. Mutation of CSB, CSA, or the TFIIH helicases XPB and XPD can also cause defective TCR and CS. We show that XPG interacts with elongating RNA polymerase II (RNAPII) in the cell and binds stalled RNAPII ternary complexes in vitro both independently and cooperatively with CSB. XPG binds transcription-sized DNA bubbles thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
188
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(197 citation statements)
references
References 63 publications
8
188
0
1
Order By: Relevance
“…Recent in vitro studies suggested that XPG might play an important role in the assembly of the TC-NER complex as XPG interacts with stalled RNAPIIo both independently and cooperatively with CSB [77]. Nonetheless in the context of chromatin, XPG appears to act downstream of CSB in TC-NER complex formation [41].…”
Section: Cs Proteins Associate With Uv-stalled Rnapiiomentioning
confidence: 99%
See 2 more Smart Citations
“…Recent in vitro studies suggested that XPG might play an important role in the assembly of the TC-NER complex as XPG interacts with stalled RNAPIIo both independently and cooperatively with CSB [77]. Nonetheless in the context of chromatin, XPG appears to act downstream of CSB in TC-NER complex formation [41].…”
Section: Cs Proteins Associate With Uv-stalled Rnapiiomentioning
confidence: 99%
“…As mentioned above, several studies suggest that the mammalian TC-NER complex is built up without displacement of RNAPIIo [41,70,71,77]. Importantly, the stalled RNAPIIo at the lesion may not be a sufficient barrier to prevent the DNA lesion from being accessible to repair proteins [54,71].…”
Section: Transcription Restart: a Crucial Role For Tfiis?mentioning
confidence: 99%
See 1 more Smart Citation
“…6 This finding may suggest a DNA damage recognition mechanism in which XPG initiates the recruitment of repair factors to remodel the stalled transcription bubble to repair lesions encountered by the elongating polymerase. 66 As with XPC, XPG also interacts with proteins from the BER pathway, in this case Nth1. Nth1 is a DNA glycosylase-AP lyase involved in repairing thymine glycol lesions and other types of BER lesions.…”
Section: Cutting It Out: Xpg and Xpfmentioning
confidence: 99%
“…Another study has suggested that XPG interacts directly with RNA polymerase II pointing to an earlier role of the protein in TC-NER in cooperation with the CSB protein. 46 The detailed mechanism of TC-NER and the role of XPG in this process are still not fully resolved and continue to be an active area of research. 47 …”
Section: Discovery and Cloning Of Xpgmentioning
confidence: 99%